2009
DOI: 10.1016/j.chembiol.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Photocleavage of the Polypeptide Backbone by 2-Nitrophenylalanine

Abstract: Summary Photocleavage of the polypeptide backbone is potentially a powerful and general method to activate or deactivate functional peptides and proteins with high spatial and temporal resolution. Here we show that 2-nitrophenylalanine is able to photochemically cleave the polypeptide backbone by an unusual cinnoline forming reaction. This unnatural amino acid was genetically encoded in E. coli, and protein containing 2-nitrophenylalanine was expressed and site specifically photocleaved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 21 publications
3
64
0
3
Order By: Relevance
“…For example, this approach has been used to cross-link membrane protein ligands, such as G protein-coupled receptor peptide ligands, in S. cerevisiae (42). Finally, to selectively cleave proteins with light, o-nitrophenylalanine (18) has been genetically encoded, which results in the site-specific scission of the protein backbone through a light-induced radical mechanism (43).…”
Section: Expanded Genetic Codementioning
confidence: 99%
“…For example, this approach has been used to cross-link membrane protein ligands, such as G protein-coupled receptor peptide ligands, in S. cerevisiae (42). Finally, to selectively cleave proteins with light, o-nitrophenylalanine (18) has been genetically encoded, which results in the site-specific scission of the protein backbone through a light-induced radical mechanism (43).…”
Section: Expanded Genetic Codementioning
confidence: 99%
“…Our main rationale of using this photolabile group was because of its commercial availability, as well as its known photolysis mechanisms [34]. Peters et al have shown that photolysis of acetylated peptides containing 2-NPA leads to the cleavage of peptide backbone and produces a C-terminal carboxylate group and an N-terminal cinnoline group (Scheme 1C) [34]. It is worth noting that other photo-sensitive motifs (e.g., o -nitrobenzyl groups) could also be used to achieve UV-mediated photocleavage.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a wide range of chemical functionalities have been introduced into proteins via unnatural amino acids including, azides, alkynes, fluorophores, photosensitive moieties, and metal binders to name a few. [4][5][6][7][8][9][10][11] Specifically, modifying proteins with fluorescent probes provides the ability to examine structure and function of proteins as well as visualize their cellular location via fluorescence spectroscopy. 12 Numerous fluorescent probes have been utilized within a protein context to further advance our understanding of proteins.…”
Section: Introductionmentioning
confidence: 99%